IMPLEMENTASI PERANAN PENDAMPING DESA DALAM PENGAWASAN PEMERINTAH DESA DI KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Faradillah Paratama; Herviani (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2021)
A village assistant is a competent person assigned to assist the village in the development and empowerment of village communities. The purpose of this study is to determine the form of implementation of the role of village assistants in supervising the operation of the village government as per the laws and regulations. This study uses a legal research type with an empirical approach, where data is obtained directly from the field through interviews and observations, the data obtained are analyzed qualitatively and then described descriptively. The results of the study indicate that the implementation of the role of village assistants has brought changes in the development and empowerment of village communities in Marioriwawo District, especially in equitable development and efforts to increase human resources in the village and are carried out according to the guidelines regulated in the village law along with other implementing regulations.